The Corporate Governance of South African State-Owned Enterprises (SOEs): Leadership and Compliance Issues - PETERSEN, Robin; DUBIHLELA, Jobo; CHAKABVA, Oscar (PT Keberlanjutan Strategis Indonesia, 2024)
The financial, operational, and business issues facing SOEs have reduced the trust that investors and citizens have in the state's capacity to effectively promote national economic growth. Most countries, especially developing ones like South Africa, have been plagued by the issue of inadequate public service delivery. One key contributing factor to this problem has been identified as the poor governance practices of SOEs. The magnitude of these massive SOE business failures, which surpassed the failure of numerous other enterprises around the world, drew attention to the urgent need for new corporate governance studies. To contribute to this, the study explores the corporate governance of South African SOEs, with a focus on leadership and compliance. To achieve this, an online questionnaire was used to gather quantitative data from a sample of 288 internal audit professionals. The data collected was then analyzed using SPSS software, and descriptive statistics were employed to present the findings. The study found that corporate governance malpractices are common in SOEs, which include hiring managers and executives who lack the necessary qualifications and experience, high tender irregularities, and understaffing critical duties. This study is unique in that it employs stakeholder theory in an innovative approach to explain the findings, notably on the leadership issue. Besides, it contains critical recommendations for SOE leadership and policymakers on how to improve the corporate governance of SOEs to help them achieve their strategic goals, while also suggesting future study directions.